Argilominerais modificados com espécies de vanádio e titânio aplicados para adsorçao de cloridrato de amilorida e fotodegradação de tetraciclina - Oliveira, Leandro Severino de (2022)
Environmental remediation by adsorption and photodegradation have been expanded in recent years due to the demand for new treatments from the presence of emerging contaminants in water. In present study, the interaction of amiloride and vanadyl (VO+) exchanged bentonites and the photostability of tetracycline (TC) adsorbed on raw bentonite and raw vermiculite, and also in vanadium oxide and vanadium and titanium oxides clay minerals were investigated. The materials were characterized by X-ray diffraction, X-ray fluorescence, infrared spectroscopy, UV-visible spectroscopy, X-ray spectroscopy, textural analysis by N2 adsorption, zero charge potential and electron scanning microscopy coupled with energy dispersive spectroscopy (EDS) mapping analysis. Sodium bentonite (Bent-Na+) interacted with VO+ in the proportions of 100% (BentV1), 300% (BentV3) and 500% (BentV5) of the cation exchange capacity (CEC) of the clay and the matrices were subsequently applied amiloride removal from solution. The characterizations indicated that VO+ cations were incorporated into Bent-Na+, mainly by ion exchange with interlayer sodium. Amiloride adsorption occurred at pH 5.8 in 20 min, whose maximum removal was 457.08; 374.64; 102.56 and 25.63 mg g-1 for Bent-Na+, BentV1, BentV3 and BentV5, respectively. The BentV3 and vermiculite (Verm) exchanged with VO+ at 300% of the CEC were calcined for 4 or 6 h at 300 or 500 °C at 10 °C min-1 to form the VxOy supported in the clay minerals, being that oxide formation occurred at 500 °C for 6 h. The VO+ solids reacted with titanium isopropoxide in a basic pH and calcined under the same conditions in order to obtain TiO2/VxOy anchored in the clay minerals. XPS spectra indicated the formation of V2O5, which EDS mapping indicated the V and T uniform distribution on the surface of both minerals, with anchoring of the oxides on the surface of Verm and the interlayer region of montmorillonite. The oxide modified solids were loaded with 500 mg L-1 TC aqueous solution and the systems were irradiated with a mercury vapor lamp (without bulb) of 125 W UV-C for 100 h. The loaded and irradiated solids were subsequent exchanged with ammonium organic cation, and the supernatants were analyzed by liquid chromatography coupled to mass spectrometry, in order to elucidate possible photoproducts generated after photo exposure. TC adsorption values were 165.7, 76.4, 43.9 and 30.4 for Bent-Na+, VermVxOy, Verm and BentVxOy, respectively. However, better photostability was observed for both raw matrices than the VxOy matrices, whose degradation values were 42; 71, 89.5 and 94.8% for Bent-Na+, Verm, BentVxOy and VermVxOy, respectively. Therefore, the presence of V2O5 improved the TC degradation. In mixed systems, better photodegradation occurred in BentVxOyTiOx (69.4%) compared with VermVxOyTiOx (66.6%). The reactions were successfully performed, suggesting that the pre-exchange of clays with VO+ resulted in adsorbents for amirolide and/or precursors for the formation of V2O5, with or without the presence of TiO2, which altered the photostability of the previously adsorbed TC.